Translating rights and articulating alternatives: rights-based approaches in ActionAid's work on unpaid care. Issue 5 (28th May 2019) - Kelly, Ruth
ABSTRACT: The adoption of a rights-based approach at ActionAid has transformed the non-governmental organisation's structure, processes and priorities. Yet the organisation may have underestimated the tension between pre-existing participatory work and rights-based approaches, and between grassroots definitions of rights and the rights prioritised in national and international advocacy and campaigning. By looking at the evolution of ActionAid's work on unpaid care, we can see how the organisation has built on work translating rights to make them relevant for local communities and begun to promote alternative articulations of rights and of rights-based approaches inspired by participatory work with communities.